1964
DOI: 10.1126/science.145.3627.55
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycins and Porfiromycin: Chemical Mechanism of Activation and Cross-linking of DNA

Abstract: Mitomycins and porfiromycin, generally nonreactive in the natural oxidized state, behave as bifunctional "alkylating" agents upon chemical or enzymatic reduction, followed by spontaneous loss of the tertiary methoxy (hydroxyl) group and formation of an aromatic indole system. Thus activated, mitomycins and porfiromycin react in vitro with purified DNA, linking its complementary strands. A high content of guanine and cytosine favors this cross-linking reaction, which is the basis of the lethal effect in vivo of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
270
0

Year Published

1966
1966
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 557 publications
(275 citation statements)
references
References 11 publications
5
270
0
Order By: Relevance
“…When interpreting these results, it is important to consider that although it is unlikely that MMC will trigger lesions within the EGFP coding region, the survival assay is monitoring the effect of MMC-induced interstrand cross-links (ICLs) in the whole genome. Given that ICLs, although representing only one MMC-DNA adduct out of many, are the major source of cytotoxicity (28)(29)(30)(31), it is tempting to speculate that the survival assay is revealing the contribution of p53 to the resolution of ICLs. It is interesting that this scenario is different from the one observed after introduction of DSBs by ionizing radiation (IR).…”
Section: Resultsmentioning
confidence: 99%
“…When interpreting these results, it is important to consider that although it is unlikely that MMC will trigger lesions within the EGFP coding region, the survival assay is monitoring the effect of MMC-induced interstrand cross-links (ICLs) in the whole genome. Given that ICLs, although representing only one MMC-DNA adduct out of many, are the major source of cytotoxicity (28)(29)(30)(31), it is tempting to speculate that the survival assay is revealing the contribution of p53 to the resolution of ICLs. It is interesting that this scenario is different from the one observed after introduction of DSBs by ionizing radiation (IR).…”
Section: Resultsmentioning
confidence: 99%
“…Mitomycin C. Since the report by Iyer and Szybalski (1964), the requirement for redox biotransformation of mitomycin C (MMC) has been well recognized in pharmacology, because MMC must be activated by a series of redox reactions leading to semiquinone derivatives coupled with ROS formation (Dusre et al 1990;Gutteridge et al 1984;Penketh et al 2001;Pritsos and Sartorelli 1986). Well-established mechanistic information has shown that MMC-associated toxicity is dependent on oxygen levels (Clarke et al 1997;Korkina et al 2000) and is removed by low-molecularweight antioxidants (Raj and Heddle 1980) and by thioredoxin (Trx) overexpression (Ruppitsch et al 1998).…”
Section: Xenobiotics Involved In Defining Fa Phenotypementioning
confidence: 99%
“…A salient feature of the molecular mechanism of action of MC is that this agent exists as a prodrug, and both its DNA crosslinking and monoalkylating activities require the reduction of the quinone ring to a hydroquinone, which transforms MC into a highly reactive alkylating species (11). Enzymes known to activate MC to intermediates capable of alkylating DNA do so either by a one-or a two-electron reduction mechanism.…”
mentioning
confidence: 99%